2016
DOI: 10.1016/j.jcot.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Concepts in regenerative medicine: Past, present, and future in articular cartilage treatment

Abstract: Regenerative medicine is emerging with great interest and hope from patients, industry, academia, and medical professionals. Cartilage regeneration, restoration, or repair is one of the prime targets that remains largely unsolved, and many believe that regenerative medicine can possibly deliver solutions that can be widely used to address the current gap(s) in treatment. In the United States, Europe, Australia, and India the regulation of regenerative based treatments has become a big debate. Although the rule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…These hurdles may prevent the implementation of such therapies in everyday practice. 20 Furthermore, the process of stem cell procurement, gene transfection, and development of these treatment injections often come with considerably costs, which have yet to be justified for widespread clinical use. 21 However, in Tan et al's evaluation of the cost of tissue engineering, it was found that these methods may actually be associated with lower costs than using material from donors.…”
Section: Discussionmentioning
confidence: 99%
“…These hurdles may prevent the implementation of such therapies in everyday practice. 20 Furthermore, the process of stem cell procurement, gene transfection, and development of these treatment injections often come with considerably costs, which have yet to be justified for widespread clinical use. 21 However, in Tan et al's evaluation of the cost of tissue engineering, it was found that these methods may actually be associated with lower costs than using material from donors.…”
Section: Discussionmentioning
confidence: 99%
“…Eligible articles were written in English and analyzed the therapeutic injection effects of PRP, prolotherapy, or MSCs via intradiscal, facet joint, epidural, or SIJ delivery on human patients diagnosed with spine‐related pain. PRP, prolotherapy, and MSCs were the 3 orthobiologic agents chosen to include within this review because they are the most common agents used for regenerative injection‐based therapy in musculoskeletal medicine and are the most well studied . Exclusion criteria were case reports and studies in which spine‐related pain was not the principal diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…PRP, prolotherapy, and MSCs were the 3 orthobiologic agents chosen to include within this review because they are the most common agents used for regenerative injection-based therapy in musculoskeletal medicine and are the most well studied. 22 Exclusion criteria were case reports and studies in which spinerelated pain was not the principal diagnosis. Three authors (D.R., J.T.M., B.M.)…”
Section: Methodsmentioning
confidence: 99%
“…Ideally, this is achieved by implanting a sufficient number of mature chondrocytes or undifferentiated progenitor cells with a high chondrogenic potential [6]. Recently, experimental therapies using mesenchymal stem cells (MSCs) have been receiving an increasing amount of interest, mostly due to the ease of isolation and their regenerative potential [7][8][9]. Unfortunately, the use of native unaltered chondrogenic cells, either chondrocytes or MSCs, has not fulfilled expectations, with the underlying mechanisms of tissue regeneration still poorly understood [10].…”
Section: Introductionmentioning
confidence: 99%